find roots of 2x²+x-6
Answers
Answered by
3
Answer:
2
x
−
3
)
(
x
+
2
)
=
0
If any individual factor on the left side of the equation is equal to
0
, the entire expression will be equal to
0
.
2
x
−
3
=
0
x
+
2
=
0
Set the first factor equal to
0
and solve.
Tap for more steps...
x
=
3
2
Set the next factor equal to
0
and solve.
Tap for more steps...
x
=
−
2
The final solution is all the values that make
(
2
x
−
3
)
(
x
+
2
)
=
0
true.
x
=
3
2
,
−
2
image of graph
Answered by
1
Answer:
the solution is in the photo
Attachments:
![](https://hi-static.z-dn.net/files/dc8/0e8cb55817f6b842b916d740273190e2.jpg)
Similar questions
Math,
5 months ago
Math,
5 months ago
Math,
5 months ago
Hindi,
10 months ago
Social Sciences,
1 year ago